A study on the effectiveness of training programs offered by ATCEN / Siti Salwa Azeni - Azeni, Siti Salwa (2009)
This study focused about how the effectiveness of training programs that is provided by ATCEN. There are four objectives on this study. The first objective of this study is to identify the level of training effectiveness towards the training offered by ATCEN. Second, to determine the factors influence the effectiveness of training in ATCEN. Third is to determine the most influence factor that contribute to the effectiveness of training offered by ATCEN. And last but not least is to give recommendation to improvise further on the effectiveness of training offered by ATCEN. This objective can be identified by the trainer’s professionalism, skills and knowledge of trainers, the module content to conduct training and also about facilities provided for the training. For this study, the researcher used descriptive research, exploratory research and causal research. Probability method will use to complete this research and the researcher use primary data to obtain reliable data. Target populations for this study are 100 respondents and 80 respondents will be select randomly. The questionnaire will distribute to the clients of the training to get the best result in getting the effectiveness of training. The method used for collection data are internet interviewing which is via email. The data was collected and analyzed by using Statistical Package for Social Science (SPSS) Program version 14.0 to get accurate answer. At the end of the study it has concluded that the training program offered by ATCEN was very effective and most of the participant satisfied with the training program. Also, the researcher has recommended some suggestion to be improved. This is beneficial to ATCEN to improve their training programs that is provided in order to achieve its vision and mission.